CATALYST COMPOSITION FOR CONVERSION OF SULFUR TRIOXIDE AND HYDROGEN PRODUCTION PROCESS - BHARGAVA, BHARAT; BANERJEE, SATINATH; UPADHYAYULA, SREEDEVI; BHASKARWAR, ASHOK NIWRITTI; KONDAMUDI, KISHORE; DAMARAJU, PARVATALU (2021)
The present disclosure relates to a catalyst composition for conversion of sulphur trioxide to sulphur dioxide and oxygen comprising an active material selected from the group consisting of transitional metal oxide, mixed transitional metal oxide, and combinations thereof; and a support material selected from the group consisting of silica, titania, zirconia, carbides, and combinations thereof. The subject matter also relates to a process for the preparation of the catalyst composition for conversion of sulphur trioxide to sulphur dioxide and oxygen.